The Development Of Holistic Model Of Character Education Management For Senior High Schools In Pemalang Regency - Prihastanto, Adi; Samsudi, Samsudi; Masrukhi, Masrukhi; Prihatin, Titi (Universitas Negeri Semarang, 2016)
The current implementation of character education has not fully succeeded in establishing the character of Indonesian people, especially high school students. The purpose of this study is to develop a holistic model of character education management for high school that can be used to enhance character education implementation in high school in Pemalang Regency. This study employed qualitative approach, starting from the preliminary stage of research and development until the test of feasibility. The variables in this study are: 1) the principal, 2) the vice principal of curriculum, 3) the subject teachers and guidance and counseling staffs, 4) head of administration, 5) parents, and 6) the school committee. The results of preliminary study show that: 1) the implementation of character education in high school in Pemalang Regency is still lacking, 2) The teaching of character education only focuses on the aspects of intellectuality, 3) All components consisting of the principal, vice-principal of curriculum, subject teachers, counseling and guidance, head of the administration, parents, and school committee still implement the character education partially, 4) an alternative solution in the development of a holistic model of character education management in high school in Pemalang Regency is needed. From these results, the lacking of character education is caused by the teachers who only pay attention to the cognitive aspect, and ignore the affective, psychomotor, and spiritual aspects of learners. In fact, students should be fostered intellectually, physically, spiritually, and affectively, involving the integration from the principal, vice principal of curriculum affairs, vice principal of student affairs, subject teachers, counseling staffs, heads of administration, parents and school committees. This is consistent with a holistic model approach.